Crossborder collaboration in African agricultural research: The political economy of technology spillovers - Roseboom, Johannes (International Food Policy Research Institute, 2016)
This chapter first presents an overview of current thinking about agricultural research spillovers; it goes on to summarize recent attempts to quantify the potential for agricultural technology spillovers globally, across SSA’s subregions, and between member countries of the subregional organizations (SROs) of national agricultural research systems (NARSs) in SSA1; it then provides an assessment of the implications of this information for regional collaboration in agricultural research. The remaining discussion focuses on benchmarking some of the key characteristics of crossborder collaboration in agricultural research in the United States, the European Union (EU), and SSA. The chapter closes with a summary of the main conclusions.